2019
DOI: 10.1021/acs.jmedchem.9b01313
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Aryl Carboxamide Derivatives as Hypoxia-Inducible Factor 1α Signaling Inhibitors with Potent Activities of Anticancer Metastasis

Abstract: In order to discover novel hypoxia-inducible factor 1 (HIF-1) inhibitors for the cancer metastasis treatment, 68 new aryl carboxamide compounds were synthesized and evaluated for their inhibitory effect by dual luciferase-reporter assay. Based on five rounds of investigation on structure−activity relationships step by step, compound 30m was discovered as the most active inhibitor (IC 50 = 0.32 μM) with no obvious cytotoxicity (CC 50 > 50 μM). It effectively attenuated hypoxia-induced HIF-1α protein accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Novel aryl carboxamide derivatives were recently reported with the most potent compound bearing IC 50 of 0.32 μM and effectively attenuated HIF-1α accumulation with reduced transcription of epidermal growth factor. [57] It also exhibited inhibitory potency on cellular migration, invasion, and capillary tube formation. Interestingly, this compound also demonstrated anti-metastatic potency in breast cancer lung metastasis in a mice xenograft model (Figure 4; compound 1).…”
Section: Progress Of Hypoxia-inducible Factor-1 (Hif-1) Inhibitorsmentioning
confidence: 96%
“…Novel aryl carboxamide derivatives were recently reported with the most potent compound bearing IC 50 of 0.32 μM and effectively attenuated HIF-1α accumulation with reduced transcription of epidermal growth factor. [57] It also exhibited inhibitory potency on cellular migration, invasion, and capillary tube formation. Interestingly, this compound also demonstrated anti-metastatic potency in breast cancer lung metastasis in a mice xenograft model (Figure 4; compound 1).…”
Section: Progress Of Hypoxia-inducible Factor-1 (Hif-1) Inhibitorsmentioning
confidence: 96%
“…First, the different substituted nitriles were reacted with hydroxylamine hydrochloride to obtain the amidoxime a [38]. Then, compound b was obtained from the reaction of intermediate a and ethyl oxalyl monochloride in acetonitrile, and then hydrolysis with LiOH in EtOH was enacted to obtain key intermediate c using methods according to previous methods in the literature [39,40]. Following this, intermediate c was reacted with oxalyl chloride to produce intermediate d [40], which in turn was reacted with the primary amine to obtain compounds F1−F24.…”
Section: Chemistrymentioning
confidence: 99%
“…The results showed that compound 30 m was the most active inhibitor with the lowest cytotoxicity. It effectively attenuated hypoxia-induced HIF-1α protein accumulation in a dose-dependent manner, which was demonstrated by its inhibitory potency on capillary-like tube formation ( Liu et al, 2019 ). In another study, cardenolides were isolated and purified from latex and giant fir fruit of Calotropis gigantea, a medicinal plant.…”
Section: Therapeutic Strategies Targeting Hif-1α In Bcmentioning
confidence: 99%